Read murga songs to have memory (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2022)
In this article we will share part of the research carried out for the Final Integrative Work within the framework of the Specialization in Writing and Literacy of the FaHCE-UNLP. We set out to investigate the recent past content teaching through reading practices in first grade. It is of a qualitative, descriptive and exploratory nature. We design a didactic sequence to promote autonomous readers about the recent past and we analyze the situations and teaching interventions that promote reading to learn. We will focus on reading situations through the teacher, on reading exchanges regarding murga songs with reference to the recent past and on the construction of memory, which give clues and provide evidence of the potential of shared readings to learn a specific content.
Keywords: recent past; memory; teaching; reading; murga songs